A clinician’s guide to understanding aortic 4D flow MRI - Mitch J. F. G. Ramaekers; Jos J. M. Westenberg; Bouke P. Adriaans; Estelle C. Nijssen; Joachim E. Wildberger; Hildo J. Lamb; Simon Schalla (Insights into Imaging, 2023)
Abstract Four-dimensional flow magnetic resonance imaging is an emerging technique which may play a role in diagnosis and risk-stratification of aortic disease. Some knowledge of flow dynamics and related parameters is necessary to understand and apply this technique in clinical workflows. The purpose of the current review is to provide a guide for clinicians to the basics of flow imaging, frequently used flow-related parameters, and their relevance in the context of aortic disease. Clinical relevance statement Understanding normal and abnormal aortic flow could improve clinical care in patients with aortic disease. Graphical abstract